Water security and food sovereignty in rural communities in Alto Jequitinhonha (Revista Espinhaço, 2023)
e article analyzes water consumption by farming families in three rural communities in Turmalina, semi-arid region of Alto Jequitinhonha, identifying possible supply strategies and rearrangements for food production and self-consumption. Data were collected through field surveys combined with semi-guided interviews. e results indicate that farming families, whose water sources were impacted by eucalyptus monoculture, seek to build access to different waters, mainly through public policies, toguarantee human consumption. In addition, they reorganize the production system to prioritize the production of food for selfconsumption, in the search for sovereignty and food security in situations of water crisis.
Keywords: Water; Self-consumption; Alto Jequitinhonha; Drought